IAIN Sultan Amai Gorontalo's Strategy to Create Local Sharia Entrepreneurs - Sulam (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
The Police Paper illustrates the suboptimal integration of the Student Creativity Program (PKM) and Community Service (PkM) at IAIN Sultan Amai Gorontalo with the local economic empowerment program. Although PTKN (State Universities) has a Tri Dharma mandate for socio-economic development, campus innovation programs tend to be purely academically oriented and stall at the reporting stage, failing to transition into sustainable business units or generate significant economic impact. The root of the problem lies in the lack of a mechanism for validating local market needs and the dominance of lab-oriented ideas disconnected from the potential of MSMEs and the sharia economy in Gorontalo. The methodology used in this paper is Qualitative-Normative Policy Analysis, with a focus on policy problem-solving. Data were collected through extensive desk research of regulatory documents (Laws, Ministerial Regulations of the Minister of Religious Affairs, and Rector's Regulations), as well as empirical studies (scientific journals) relevant to the Triple Helix Theory, Business Incubation Theory, and the Community Engagement Concept. Policy alternative analysis was conducted using the William N. Dunn Scoring Model to assess the effectiveness, efficiency, and feasibility of each regulatory option. The analysis shows that the most effective structural solution is through internal policy transformation. The main policy recommendation is the establishment of a Rector's Regulation on the Mandatory Integration of PKM into the Core Curriculum and the Credit System, supported by the Standardization of the Participatory Action Research (PAR) Approach in all community-based PKM. This policy aims to shift the academic culture to an entrepreneurial culture validated in the field, making IAIN SA Gorontalo a relevant and sustainable driving force for the people's economy.